The Effectiveness of Teaching Materials for Graphic Organizers in Reading in Elementary School Students - Otang Kurniaman; Zufriady Zufriady (Universitas Riau, 2019)
A teacher must be able to develop teaching materials in learning because it is a professional demand that can provide meaningful and enjoyable learning. The purpose of this study was to describe the effectiveness of developing graphic organizer teaching materials in reading in grade 4 of elementary school. The graphic organizer is a learning media used to read learning. This is a development research with consisting of 4 stages namely defining, designing, developing, and disseminating research results. Aspects namely need analysis and student analysis. In needs analysis, some analyzes were carried out covering curriculum, concepts, and assignments. While in the analysis of students looking at the suitability of teaching materials developed with the level of development of students. The design phase of teaching materials was made to plan the implementation of learning indicators, the average indicator was 95, and the learning objectives aspect was 93. The development phase was tested in SDN 38 Kota Pekanbaru with an average reading ability of 87.5, so it can be concluded that the effectiveness of teaching materials for graphic organizer in reading is very decent to use.